An interview with Dr. David Chng Khin Yong research studies on inscriptions and foreign language archives - Ee, Ooi Sing (Tanjong Malim, 2024)
An interview with Dr. David Chng Khin Yong research studies on inscriptions and foreign language archives by Ee, Ooi Sing